Answer:
[tex]x=\frac{1}{2},\frac{3}{2}[/tex]
Step-by-step explanation:
[tex]log_{x} (8x - 3)-log_{x} (4)=2[/tex]
We can simplify this by using the rules of logarithms to [tex]\frac{log_{x}(8x-3) }{log_{x}(4) } =2[/tex]
By using another rule of logarithms we can rewrite the equation as [tex]\frac{8x-3}{4} =x^{2}[/tex]
Then we can multiply both sides by 4 to get rid of the fraction on the left side: 8x - 3 = 4x²
Then we can move all the terms to one side so we can have a polynomial to factor out and solve for x: 4x² - 8x + 3 = 0
Factoring this we get (2x - 1)(2x - 3) = 0
Setting each individual part equal to zero we get [tex]x=\frac{1}{2},\frac{3}{2}[/tex]